Study of autopsy based suicidal hanging (Bangladesh Journal of Physiology and Pharmacology, 2015)
Introduction: Hanging is one of the most commonly used methods for suicide in most countries. Commission of suicide by hanging is increasing in the people of Bangladesh. Suicidal hanging is detrimental to social health. Appropriate measures to prevent it are essential. Objectives: To find out the demography, cause and nature of suicidal hanging. Study design: It is a cross sectional type of descriptive study. Setting: Data was collected on predesigned proformas from postmortem reports recorded by the students of DFM and MD in Forensic Medicine at Dhaka medical college during their course. Subject: Autopsy performed on the cases of suicidal hanging at Dhaka Medical College Morgue from September, 2011 to June, 2013. Result: Out of 100 cases, eighty two (82%) were female and the most commonest (50%) age group were from 11-20 years. In 18(18%) cases Dopatta were the commonest material used for hanging. Quarrel with husband 12(12%) were the predominant cause to destroy life. In ninety (90%) cases had complete suspension where the most commonest situation of gap was on the back (38.89%). During autopsy of suicidal hanging there were injuries on the body of deceased in few cases. But these injuries did not result in death of the victim. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22677 Bangladesh J Physiol Pharmacol 2014; 30(2): 14-17